A Note on the Polysemous Verb 'To Eat' in Nepali and Newar - Kansakar, Tej Ratna (Gipan, 2017)
The central idea of the present analyses of the 'eat' verb has to do with polysemy which shows diverse meaning relationships in Nepali and Newar. The multiple meanings that can be derived in various contexts have been classified and defined in terms of generative semantic rules that can derive a large number of linguistic categories in both the languages. The sources of data from Nepali and Newar also include idioms, metaphors and metonymy. These serve to indicate a typological relationship which perhaps can be extended to other Indic and Tibetic languages to illustrate the prototypical commonality between languages of the same family and those of other genetic affiliations.